Salmonella: a foodborne pathogen - Pui, Chai Fung; Wong, Woan Chwen; Chai, Lay Ching; Robin, Tunung; Ponniah, Jeyaletchumi; Mohd Sahroni, Noor Hidayah; Anyi, Ubong; Mohamad Ghazali, Farinazleen; Cheah, Yoke Kqueen; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Salmonellosis continues to be a major public health problem worldwide. It also contributes to negative economic impacts due to the cost of surveillance investigation, treatment and prevention of illness. As such, research on Salmonella has gained great interest and concern from scientists. The purpose of this review is to discuss the classification and nomenclature, characteristic, clinical manifestation, epidemiology, transmission vehicles, antibiotic resistance and quorum sensing of Salmonella.